Implementasi Manajemen Pendidikan Karakter Dalam Mengembangkan Akhlak Siswa - Sali Syawaliah; Ahmad Asrori; Nurul Hidayati Murtafiah (Najah Bestari, 2023)
Children will develop character if they are reared in an environment that fosters character and allows their natural tendencies to flourish. However, the current system of early childhood education is overly focused on the development of the left brain (cognitive skills) and gives little consideration to the development of the right brain (affective, empathy, taste). Therefore, the goal of this study is to determine how the Kindergarten Manbaul Iman Kindergarten, Wanaraja District implements Character Education Management in building student morals. This descriptive qualitative study collects data through interviews, observations, and document reviews pertaining to character education administration. After collecting data, the next stage is to analyze it by displaying data, presenting data, and generating conclusions. The study's findings indicate that the implementation of character education management in developing morals begins with the planning process for character education management for students, which involves stakeholders, committees, village heads, religious leaders, and the local community in determining the character values contained in the school's rules. The execution of character education management includes all school aspects that contribute to the creation of settings that foster the character development of pupils. This growth is the result of preventative, curative, and repressive measures. The management evaluation of character education consists of observing all teachers involved in assessing student character and taking notes on student improvement.